Keris Sebagai Representatif Manusia Dalam Peradaban Masyarakat Bali Di Lombok - Yasa, I Made Ardika; Arnyana, Ida Bagus Putu; Suastra, I Wayan (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
Keris, a traditional Indonesian weapon, plays a significant role in the civilization of the Balinese society in Lombok. Keris is not merely a weapon but also a symbol of culture, art, philosophy, and identity for the Balinese community. In this article, we explore the role of keris as a representative of humanity in the civilization of the Balinese society in Lombok. This research adopts a qualitative method, conducting field studies and interviews with community figures who possess extensive knowledge and experience regarding the Balinese keris in Lombok. The research findings indicate that the keris holds profound meaning for the Balinese society in Lombok. Firstly, the keris symbolizes a strong cultural identity. The keris serves as a marker of social status and bravery within the Balinese society. Owners of the keris are considered to have high standing and are respected by the community. Through the keris, the Balinese society in Lombok preserves and passes down their cultural values from generation to generation. The keris also represents the beauty of art. The process of crafting a keris involves high-level skills from the keris makers. The Balinese keris in Lombok features exquisite adornments, including intricate carvings and unique Balinese ornaments. The artistic beauty of the keris serves as an expression of the Balinese community's creativity. In conclusion, the keris holds significant meaning as a cultural symbol and an artistic expression for the Balinese society in Lombok. It represents their cultural identity, social status, bravery, and artistic creativity. This research sheds light on the profound role of the keris as a representative of humanity within the civilization of the Balinese society in Lombok.